Effect of pentanol-biodiesel blends on performance and emission characteristics of the diesel engine. Issue 8 (11th June 2021) - Jeyakumar, Nagarajan; Narayanasamy, Bose
ABSTRACT: Identification of next generation bio-fuels like pentanol has emerged as a suitable solution to increased demand for alternate sources of energy. The present work deals with the effect of pentanol addition at different concentrations with Karanja oil biodiesel on performance and emission characteristics of diesel engines. The experiments were conducted in a single cylinder, water cooled direct injection diesel engine fuelled with Karanja oil biodiesel blends along with pentanol addition of 10% and 20% by volume. The fuel properties of the test samples were found to be within the ASTM limits and can be suitably used in diesel engines. The brake thermal efficiency was found to be increased and brake specific fuel consumption decreased with pentanol addition to Karanja oil biodiesel. Furthermore, the diesel engine fuel with oxygenated fuel blends reduced the CO, HC, smoke emission along with NO x emission and EGT due to the higher latent heat of vaporisation of pentanol and increase in CO2 .